Is the European Community facing a fresh financial crisis? - Gerhard Stahl (Intereconomics, 1992)
The further development of the European Community that has been decided at the Maastricht summit will be impossible to realize without a significant increase in the EC budget and an adjustment to the financing system. What will be the additional financing requirement? How could the Community's financing system be reformed?
Keywords: 330; European Community